SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN REWARD TENAGA KURIR DI SICEPAT EKSPRES DENGAN METODE PROFILE MATCHING - Ismail Abdurrazaq Zukarnain; Fajar Harianto; Sugianti Sugianti (Universitas Muhammadiyah Ponorogo, 2022)
Humans in this life will work to survive or fulfill their needs and survival. Likewise, for the expedition employee for shipping goods at Sicepat Ekspres, this additional reward income is to motivate couriers to perform better. However, the problem that occurs in the process of giving employee rewards at the Sicepat Ekspres Madiun Mejayan branch is still manual, so that giving rewards is inefficient and the subjectivity factor tends to be high due to the absence of integrated and less effective supporting data. With this problem, the author has an idea to create a decision support system for giving employee rewards. In this system displays the reward that has been defined in the system. The method made in this system is the Profile Matching method. With this method, which is an algorithm for the decision-making process based on ideal variables and identification of employees who have good or bad performance. From the results that have been tested by doing it on this system, it can run properly and properly. This system can display the process of rewarding employees who have met the criteria needed to reward courier workers at Sicepat Ekspres.